Beyond Cultural Differences and Similarities: Student Teachers Encounter Aboriginal Children’s Literature - Doige, Lynda (Canadian Journal of Education/Revue canadienne de l'éducation, 1999)
This article examines teacher education students’ interactions around a course in Aborig- inal children’s literature. Observations of these students suggest that expressing and ex- ploring ideas and feelings about issues like stereotyping helps them develop a supportive kinship, which promotes learning that transforms attitudes. Some questions explored in this article are: (1) What is effective learning in a multicultural classroom? (2) How can teachers and students become learning partners in the multicultural classroom? (3) What is the difference between understanding culture and valuing people? This exploration may assist teachers to identify changes in students’ social, cognitive, and emotional develop- ment within the context of a growing community of learners from various cultures. Teachers may also find the students’ evaluation of the classroom atmosphere and dy- namics useful in gathering and preparing material for multicultural settings. Dans cet article, l’auteure analyse les interactions d’un groupe d’étudiants-maîtres au sujet de la littérature pour enfants en milieu autochtone. Les remarques de ces étudiants donnent à penser que le fait d’exprimer et d’explorer des idées et des sentiments sur des questions comme les stéréotypes les aident à tisser des liens qui favorisent l’apprentissage et transforment les attitudes. L’article aborde les questions suivantes : (1) Qu’entend-on par un apprentissage efficace dans une classe multiculturelle? (2) Comment les ensei- gnants et les élèves peuvent-ils créer des partenariats d’apprentissage dans une classe multiculturelle? (3) Quelle est la différence entre comprendre une culture et valoriser les personnes? Cette réflexion peut aider les enseignants à identifier les changements dans le développement social, cognitif et émotif des élèves au sein d’une communauté grandis- sante d’apprenants de diverses cultures. Les enseignants peuvent également trouver l’évaluation de l’atmosphère et de la dynamique de la classe par les élèves utile pour la recherche et la préparation de matériel destiné à des classes multiculturelles.